3D (Demand Driven Development) Program: Industry-Academia Collaboration (IAC) for the E&E Sector-IC Design Cluster leading by CEDEC, USM - CEDEC, Pusat Usahasama Kecemerlangan Rekabentuk Mikroelektronik (2015)
Talent Corporation Malaysia has appointed CEDEC, USM as a Manager for 3D Programme for the period of two years starts from 2016. 3D stands for Demand, Driven and Development aims to expedite all participation universities to raise the level of excellence in higher education focusing in the area of IC design. Therefore, one of the objectives of this programme is to build a network of universities that capable of producing Intellectual Property(s) for System on Chip (SoC) and IC Design that creates the funnel of industry ready graduates for the IC Design Cluster.